Integrated morphological, physiological, and transcriptomic analyses uncover the mechanisms of waterlogging tolerance in Sorghum bicolor (L.) - Zhang, Ruidong; Chen, Haiyun; Li, Xiang; Wang, Minli; Luo, Yu; Jiao, Wenda; Chang, Jiarong; Cao, Xiong; Feng, Jun (Frontiers in Plant Science, 2025)
Sorghum (Sorghum bicolor L.) is a vital global crop often cultivated in waterlogging-prone regions. However, its productivity is severely limited by waterlogging stress, which inhibits growth and significantly reduces yields. To address this, we investigated the physiological and molecular mechanisms of waterlogging tolerance by comparing a tolerant variety ‘S208’ with a sensitive one ‘S015’. After 12 days of waterlogging, ‘S208’ exhibited markedly less reduction in plant height, stem thickness, and leaf area. It also developed more and longer adventitious roots and, after 6 days, formed a significantly higher proportion of aerenchyma Physiological assays revealed that the activities of key anaerobic respiratory enzymes, including pyruvate decarboxylase (PDC), lactate dehydrogenase (LDH), and alcohol dehydrogenase (ADH), were consistently higher in ‘S208’. Transcriptomic analysis 24 hours post-waterlogging identified differentially expressed genes (DEGs) enriched in energy metabolism, hormone regulation, and cell wall modification. Weighted gene co-expression network analysis (WGCNA) further highlighted the predominant regulatory roles of AP2/ERF, BHLH and WRKY transcription factor families. Our finding demonstrate that the superior waterlogging tolerance of ‘S208’ is atrributed to integrated morphological, phsiological, and transcriptional adaptations, providing valuable insights for breeding resilient sorghum varieties.